Views and behaviours of municipal actors relating to climate change and water management: the case of local municipal water management and social networks - Gerstner, Kristian (Department of Environmental and Geographical Science, 2020)
Climate change is projected to impact the hydrological cycle and have a negative effect on water supply. In South Africa, water to the end user is supplied by local municipalities, and thus municipalities are likely to benefit from adapting to these climate impacts. This research aims to understand the views and behaviours of local municipal actors towards water management and climate change, and how these views and behaviours influence the resilience of their water supply system in the face of climate change. A secondary aim of the thesis was to determine if the advice networks, where the actors receive the bulk of their information from, influenced the actor’s views and behaviours around water management, climate change, and adaptation, using a social network approach. The study area focused on five local municipalities in the West Coast District of South Africa. This research made use of a mixed methods approach, utilising both qualitative and quantitative data, obtained using semi-structured interviews with a structured component. Qualitative data were used to collect water management-related views and behaviours of municipal actors, whilst quantitative data were collected to determine social network characteristics. The views and behaviours on water demand and supply management of the actors interviewed tended to differ. Actors’ views on ideal water management approaches were more concerned with the long-term sustainability of water resources through raising awareness and managing existing infrastructure better. Actor’s preferred behaviours however focused on immediate relief to water shortages, by augmenting existing supply and enforcing restrictions. These findings imply that actors respond reactively to drought, and not proactively. In terms of climate change, actors showed a clear understanding of climate change and its risks to water management. Actors understood how climate change adaptation could be used to make their municipalities’ water supply more resilient, by utilising sustainable sources of water or through ecosystem-based adaptation, however it was found that municipal plans and behaviours did not generally reflect these views. Social network characteristics such as strengths of ties, and the existence of multiplex ties, did not appear to influence the sharing of behaviours or views between the actor and their given advice network. It was thus theorised that institutional lock-in and hierarchical governance might play a larger role in influencing views and behaviours than the actors’ social networks. The reactive responses by actors to issues of water demand or supply can lead to poor resilience in the face of climate change, where cases of drought and water shortages may become more frequent. Whilst municipal actors are aware of these changing conditions and risks, the limitations placed on them by governance structures and lock-in impact their ability to be proactive. More work needs to be done to ensure sustainable and resilient water management interventions are implemented at the local municipal level. Additionally, lockin, both institutional and technological, could usefully be challenged to allow for innovative ideas to enter the realm of water management at the local municipal level.